Partitioning kin groups of broodstock in the critically endangered Chinese sturgeon, Acipenser sinensis Gray 1835. (28th January 2018) - Xu, N.; Shao, K.; Yan, S.; Shi, F.; Zhu, B.; Chang, J.
Summary: Pedigrees of broodstock with unknown relationship of the critically endangered Chinese sturgeon, Acipenser sinensis, was evaluated using microsatellite markers to facilitate genetic management in restocking programs with small broodstock size. We characterized the distributions of relatedness values to reconstruct kin groups in four hatchery families with known pedigrees using microsatellites. The distributions of relatedness values for kin classes were used for partitioning full sibling groups of wild A. sinensis broodstock kept in two hatcheries, resulted in 13 full sibling clusters, four of which containing 62% of all the wild individuals. This indicates high probability of choosing close related breeder pairs in random mating, thus selective breeding is necessary to minimize inbreeding and maintain genetic diversity. This study provides a useful tool for genetic management in conservation programs of A. sinensis in aim of preserving self‐sustained wild populations.